2014
DOI: 10.1038/nn.3635
|View full text |Cite
|
Sign up to set email alerts
|

Resolving human object recognition in space and time

Abstract: A comprehensive picture of object processing in the human brain requires combining both spatial and temporal information about brain activity. Here, we acquired human magnetoencephalography (MEG) and functional magnetic resonance imaging (fMRI) responses to 92 object images. Multivariate pattern classification applied to MEG revealed the time course of object processing: whereas individual images were discriminated by visual representations early, ordinate and superordinate category levels emerged relatively l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

122
949
5

Year Published

2015
2015
2018
2018

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 745 publications
(1,076 citation statements)
references
References 52 publications
122
949
5
Order By: Relevance
“…We found that the time course rose sharply after image onset, reaching significance at 50 ms (45-52 ms) and a peak at 97 ms (94-102 ms). This indicates that single scene images were discriminated early by visual representations, similar to single images with other visual content (Thorpe et al, 1996;Carlson et al, 2013;Cichy et al, 2014;Isik et al, 2014), suggesting a common source in early visual areas (Cichy et al, 2014).…”
Section: Neural Representations Of Single Scene Images Emerged Earlymentioning
confidence: 84%
See 4 more Smart Citations
“…We found that the time course rose sharply after image onset, reaching significance at 50 ms (45-52 ms) and a peak at 97 ms (94-102 ms). This indicates that single scene images were discriminated early by visual representations, similar to single images with other visual content (Thorpe et al, 1996;Carlson et al, 2013;Cichy et al, 2014;Isik et al, 2014), suggesting a common source in early visual areas (Cichy et al, 2014).…”
Section: Neural Representations Of Single Scene Images Emerged Earlymentioning
confidence: 84%
“…We characterized the emerging representation of scenes in the human brain using multivariate pattern classification methods (Carlson et al, 2013;Cichy et al, 2014) and representational similarity analysis (Kriegeskorte, 2008;Kriegeskorte and Kievit, 2013) on combined MEG and computational model data. We found that neural representations of individual scenes and the low-level image property contrast emerged early, followed by the scene layout property scene size at around 250 ms.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations